Gambaran Pola Asuh Ibu Karir dan Ibu Rumah Tangga di Pekanbaru - Rodia Afriza; Athalla Fallah Navra; Idzhari Rahman (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study is to find out how the picture of mother care care career and housewife. The number of samples in this study were 540 people, 270 for working mothers and 270 for mothers not working in Pekanbaru city. The sampling technique uses quota sampling by determining the number of quotas at the significant level 10% of the total population of career mothers 153,945 people and the total population of housewives 134,345 in the city of Pekanbaru. Technique of collecting data using questionnaire which amounted to 10 items arranged based on the dimension of parenting and data analyzed with descriptive quantitative percentage. Based on the results of quantitative descriptive analysis of the study, it is known that the mother's parenting pattern that works mostly apply the authoritative parenting pattern with very high criteria, and the unemployed mother is known to mostly implement the authoritative parenting pattern, with very high criteria. Given the results of data analysis that there is no difference in the application of parenting patterns between working mothers and mothers who do not work. Factors causing no difference in parenting pattern between career mothers and housewives is the factor of the number of children, age factor and educational factors.